Design of The Heyzine Flipbook Interactive E-Module Based on SDGs for The Course Fundamentals of Islamic Science - Sabarni Sabarni; Chusnur Rahmi; Raudhatul Maghfirah (Department of Chemistry Education, Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2025)
This research aims to develop and test the validity and effectiveness of an interactive Heyzine Flipbook e-module based on SDGs for the course fundamentals of islamic science. This research uses the Research and Development method with the ADDIE approach. The subjects are 20 students from the Chemistry Education Study Program. The data was collected using a needs questionnaire, a validity questionnaire, a student response questionnaire, and a student ability test. The research results show that e-module has a very high validity level with an Aiken’s V index of 0.98, it is declared very suitable for use in learning. Based on the hypothesis test using the Wilcoxon Signed-Rank Test, a p-value of 0.000084 < 0.05 proving a significant difference between the students' pretest and posttest scores. The effectiveness of e-modul is also reinforced by the acquisition of an N-Gain score of 0.76 (high category) and effect size of 0.458 (moderately effective). Based on these findings, the Heyzine Flipbook interactive e-module based on the SDGs was very well received by students and proved effective in significantly improving learning outcomes in the course.